Effect of osteosarcopenia on feeding status in hospitalized patients with suspected dysphagia. - Midori Miyagi; Hideki Sekiya; Satoru Ebihara (PLoS ONE)
Objectives Osteosarcopenia is a combination of sarcopenia and osteoporosis that increases mortality rates among older people compared with either alone. This study aimed to identify the contribution of osteosarcopenia to the development and severity of dysphagia. Methods We retrospectively reviewed the medical charts of 211 patients aged ≥ 65 years who were referred to the dysphagia rehabilitation team. Based on Functional Oral Intake Scale (FOIS) scores, we classified the patients with (FOIS scores 1-5) and without (FOIS scores 6, 7) dysphagia as Type A and those with (FOIS scores 1, 2) and without (FOIS score 3-7) enteral feeding as Type B. Based on chest computed tomography (CT) findings we then defined patients with T4 (MI) and pectoralis (PMI) muscle indexes, L1 attenuation, and T4MI, PMI, and L1 attenuation below the cutoff values as having sarcopenia, osteoporosis, and osteosarcopenia, respectively. Results The FOIS scores were significantly lower among patients with osteosarcopenia than among those without sarcopenia or osteoporosis. Moreover, PMI and FOIS scores significantly and positively correlated, and PMI was significantly lower in the group with, than without, enteral feeding. Osteoporosis and osteosarcopenia were significant in the patients who were fed enterally (p = 0.032 and 0.047, respectively). Conclusions Patients with sarcopenia and osteoporosis undergoing swallowing rehabilitation tended to have severe dysphagia that required much medical attention.